"Fix the Workplace, Not the Worker": Labour Feminism and the Shifting Grounds of Equality in the US Workplace, 1960–91. (1st November 2020) - Faue, Elizabeth; Rector, Josiah; Walter, Amanda Lauren
Abstract : The US Supreme Court decision in UAW v. Johnson Controls, a landmark case that eliminated employer policies that excluded women from jobs with significant reproductive risks, has been the focus of considerable debate. While challenging policies that decided what risks were acceptable for women of childbearing age, critics charged that the ruling weakened labour law protections for women in the USA and lowered standards for all workers. Yet, the case emerged at a time when workplace protections under the Occupational Health and Safety Administration were already failing due to deregulation and unions were running into growing employer hostility. This article argues that labour feminists in the United Auto Workers (UAW) hoped to simultaneously force employers to end sex discrimination and toxic exposures in the workplace. They only shifted to the narrower legal strategy that prevailed in Johnson Controls in the late 1970s and 1980s for pragmatic reasons. Using equal opportunity provisions of the Civil Rights Act was one way for union plaintiffs to ensure that employers were not using foetal protection policies as an end-run around a safer workplace for all workers. Yet, while women workers and unions originally sought to "fix the workplace, not the worker, " conservative opposition accepted women having fewer labour protections while endorsing a less protected and riskier workplace.